First record of microplastic in the Brazilian sea hare Aplysia brasiliana Rang, 1828 (Mollusca: Aplysiidae) - Yapuchura Ocaris, Enrique Ronald (2023)
The presence of plastic debris in the marine environment has reached massive levels in the past decades. In marine environments, microplastics can exist for hundreds of years and the presence of microplastics in this environment has been reported since 1970 and since then has been considered ubiquitous. Mollusks are being used as microplastic pollution indicators, especially in coastal areas and bivalves are more often used in microplastic-monitoring studies. On the other hand, gastropods are poorly used as indicators for microplastic pollution, even though they are the most diverse group of mollusks. The sea hares of the genus Aplysia are herbivorous gastropods, important model organisms commonly used in neuroscience studies, isolating the compounds in their defensive ink. Until today, there is no previous record of the presence of MPs in Aplysia gastropods. Therefore, this study aims to investigate the presence of microplastics in tissues of A. brasiliana found in southeastern Brazil. We collected seven individuals of A. brasiliana from a beach in southeastern Brazil, dissected them to isolate the digestive tract and the gills, and digested the tissues with a solution of 10 % NaOH. In the end, 1021 microplastic particles were found, 940 in the digestive tissue, and 81 in the gills. These results represent the first record of the presence of microplastics in the Brazilian sea hare A. brasiliana.